Trans-splicing of mRNAs links gene transcription to translational control regulated by mTOR - Danks, Gemma B; Galbiati, Heloisa; Raasholm, Martina; Torres Cleuren, Yamila N; Valen, Eivind; Navratilova, Pavla; Thompson, Eric M (BMC genomics, 2019)
BACKGROUND: In phylogenetically diverse organisms, the 5' ends of a subset of mRNAs are trans-spliced with a spliced leader (SL) RNA. The functions of SL trans-splicing, however, remain largely enigmatic. RESULTS: We quantified translation genome-wide in the marine chordate, Oikopleura dioica, under inhibition of mTOR, a central growth regulator. Translation of trans-spliced TOP mRNAs was suppressed, consistent with a role of the SL sequence in nutrient-dependent translational control of growth-related mRNAs. Under crowded, nutrient-limiting conditions, O. dioica continued to filter-feed, but arrested growth until favorable conditions returned. Upon release from unfavorable conditions, initial recovery was independent of nutrient-responsive, trans-spliced genes, suggesting animal density sensing as a first trigger for resumption of development. CONCLUSION: Our results are consistent with a proposed role of trans-splicing in the coordinated translational down-regulation of nutrient-responsive genes under growth-limiting conditions.
Keywords: genetická transkripce; savci; TOR Serine-Threonine Kinases; trans-splicing; messenger RNA; regulace genové exprese; Trans-Splicing; Transcription, Genetic; TOR serin-threoninkinasy; Female; Urochordata; zvířata; Mammals; Caenorhabditis elegans; oocyty; Nucleotide Motifs; RNA, Messenger; proteosyntéza; ženské pohlaví; Gene Expression Regulation; Animals; Oocytes; Protein Biosynthesis; nukleotidové motivy